Assessing peer teamwork competence: adapting and validating the comprehensive assessment of team member effectiveness–short in university students - Garalde, Alain; Solabarrieta, Josu; Urquijo, Itziar; Ortiz de Anda-Martín, Irati (Frontiers in Education, 2024)
The Bologna Plan has promoted competency-based training in European higher education, which requires developing accurate, appropriate assessment tools for its measurement and evaluation. This study adapted and validated the Comprehensive Assessment of Team Member Effectiveness questionnaire on teamwork competence in a university population in the Basque Country, Spain. The questionnaire was first back-translated and adapted by two experts in educational research and then completed by 642 students pursuing baccalaureate degrees in primary education and physical activity and sport sciences at the University of Deusto (215 women, 426 men; ages: 17-25 years [M = 21.5; SD = 1.3]). A confirmatory factor analysis yielded adequate goodness-of-fit indices, confirming the validity of the instrument's measurement model and indicating that it may be an appropriate tool for assessing teamwork competence among peers for university students in the Basque Country.. Teamwork competence is understood as the ability to relate to and integrate into a work group to contribute to achieving a common goal (Atxurra & Villardón-Gallego, 2015;Barraycoa & Lasaga, 2010;Mora-Vicarioli & Hooper-Simpson, 2016). It includes a sense of belonging and commitment to the team and its activity; interaction and communication among members; planning the actions to be undertaken; and the capacity for continual adaptation to achieve objectives (Torrelles et al., 2011).